MBKM Asistensi Mengajar: Penguatan Larangan Minuman Keras Bagi Siswa Melalui Poster Berbasis Canva di SMAN 2 Palangka Raya - Sulistia Wati; Noorazmah Hidayati; Cindy Dwi Rohmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This service focuses on strengthening the prohibition of alcohol among students of SMAN 2 Palangka Rayat through the use of canva application-based posters. This service was conducted in response to the challages of alcohol abuse among teenagers and the need is Service Learning, whic involves preparation, planning, and implementation stages. This service activity was aimed at Muslim students from class XI 2 and XI 3. The result of the service showed an increase in students digital skills, creaticity in designing posters, enthuasiasm for the liquor prohibiton campaign, and a better understanding of the dangers. In conclusion, this activity succeeded in raising students awareness about the dangers of alcohol through a creative an interactive approach, while developing graphic design skills and digital literacy.